2021
DOI: 10.3390/toxins13060391
|View full text |Cite
|
Sign up to set email alerts
|

Mimosa tenuiflora Aqueous Extract: Role of Condensed Tannins in Anti-Aflatoxin B1 Activity in Aspergillus flavus

Abstract: Aflatoxin B1 (AFB1) is a potent carcinogenic mycotoxin that contaminates numerous crops pre- and post-harvest. To protect foods and feeds from such toxins without resorting to pesticides, the use of plant extracts has been increasingly studied. The most interesting candidate plants are those with strong antioxidative activity because oxidation reactions may interfere with AFB1 production. The present study investigates how an aqueous extract of Mimosa tenuiflora bark affects both the growth of Aspergillus flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 62 publications
2
14
0
Order By: Relevance
“…Several plant extracts, essential oils or isolated components were found able to block aflatoxin B1 production [11,12], among them Mimosa tenuiflora aqueous extract (MAE). Contrary to what is observed using essential oils that inhibit AFB1 synthesis together with reducing fungal growth [13], MAE was shown to inhibit AFB1 in A. flavus with no impact on fungal development [14]. This result is interesting because if the extract is able to block AFB1 production without modifying fungal growth, its impact on biodiversity shall be limited.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Several plant extracts, essential oils or isolated components were found able to block aflatoxin B1 production [11,12], among them Mimosa tenuiflora aqueous extract (MAE). Contrary to what is observed using essential oils that inhibit AFB1 synthesis together with reducing fungal growth [13], MAE was shown to inhibit AFB1 in A. flavus with no impact on fungal development [14]. This result is interesting because if the extract is able to block AFB1 production without modifying fungal growth, its impact on biodiversity shall be limited.…”
Section: Introductionmentioning
confidence: 78%
“…MAE was prepared as described [14]. M. tenuiflora bark was extracted by maceration for 15 h at room temperature.…”
Section: Preparation Of M Tenuiflora Aqueous Extract (Mae)mentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the polyphenolic hydroxyl structure, the TA has various biological activities, such as antimicrobial, anti-inflammatory, anticancer, and immunomodulatory effects (10)(11)(12). Moreover, studies have shown that dietary supplementation with antioxidants, including plant extracts and tannins can protect broilers from AFB 1 -induced toxicity by enhancing the antioxidant capacity and immunity (6,(13)(14)(15)(16)). Nevertheless, it remains unclear whether dietary supplementation with TA could alleviate acute aflatoxicosis by improving the antioxidant capacity of broilers fed AFB 1 contaminated diets.…”
Section: Introductionmentioning
confidence: 99%